How legal personhood and markets can partner to help save the whale - Chami, Ralph; Bender, Michelle; Bramley, Belinda; Cosimano, Thomas; Iles, Roger; Nieburg, Dinah; Rosa, Elena; Takoko, Mere; Fullenkamp, Connel (Frontiers in Ocean Sustainability, 2024)
Recently, the Māori People of Aotearoa, Cook Islands, and Tahiti supported a resolution to endorse their ancestors, the whales, as Ocean Ambassadors to the United Nations and to protect their legal personhood. This historic move aims to help protect the whales against dangers such as ship strikes as they migrate through their South Pacific waters. This paper explores how markets can further strengthen this declaration by providing incentives that reward responsible behavior of maritime vessels as they navigate Māori waters. Legal steps needed to engender market support and extend protection to other cetaceans and localities are also discussed. By combining personhood declaration with legal actions and market-based incentives, we show how this novel approach can enhance conservation outcomes and reshape the market in favor of protecting whales, nature, and its stewards.